The Church in the modern world : essays in honour of James Sutherland Thomson - Johnston, George; Roth, Wolfgang M.W. (Toronto : Ryerson Press, 1967)
Contents. - No living with or without God, by G. MacGregor. -Transcedence: a concept under attack, by E.G. Jay. - Beyond the Philosophies of substance and process, by N.F.S. Ferre. - Edwin Muir and the incarnation by D. Mathers. - The law of Christ and "Our deepest difference, " by D.W. Hay. - The self-understanding of the Roman Catholic Church at Vatican II, by G. Baum. - Lumen gentium: the dogmatic constitution on the Church of Vatican Council II, by G. Johnston. - The Church's ministry to the world, by E.R. Fair-weather. - Church and world in Vatican II, by W.O. Fennel. - The mission of the Church and the Future of missions, by W.C. Smith.-The future of the Christian missionary enterprise, by M. Warren. -Church and university, by S. B. Frost. - Christian education redefined, by D.C. Wyckoff. - Purpose, practice, and process in theological education, by C.Fielding. - Of memory and interpretation, by C.L. Taylor. - The other side of our Atlantic, by F.K. Hare. - A dialogue between Christians and Marxists, by M. Opocensky.- Comedy- - Human and divine, by J.C. McLelland. - Communicating the Gospel, by E. Gordon. - Bibliography of James S. Thomson (p. 306-307).
Keywords: Theology -- Addresses, essays, lectures; Thomson, James Sutherland, 1892-